African institutions will lead on the road to end neglected tropical diseases - Makau-Barasa, Louise K.; Onduma, Nathan; Yotebieng, Kelly; Karutu, Carol (Frontiers in Tropical Diseases, 2023)
Globally, more than one billion people suffer from one or more neglected tropical diseases (NTDs). These diseases create enormous suffering, rob individuals of social and economic opportunities, and set-back countries’ development efforts. It is now clear that transmission and elimination of many NTDs is attainable in our lifetime. The elimination of NTDs will not happen without a concerted effort and plan to ensure that the most affected countries have a robust clinical, public health, laboratory, pharmaceutical, and research capacity to ensure that the last mile towards reaching elimination is not only reached, but sustained. This means increasing strategic investments to develop and strengthen the NTD health workforce, develop and integrate innovative diagnostic approaches, effective treatments, and responsive surveillance systems. Equally important is ensuring that people living with lifelong disabilities resulting from NTDs receive the care and support they need to live healthy, productive, and fulfilling lives. African-based national non-governmental organizations, the private sector, research institutions, and governments play a vital role as they work to attain ambitious NTD elimination and control goals put forward by the global health community. The recent elimination of onchocerciasis in Niger, trachoma in Burundi and Malawi as well as ongoing progress to eliminate lymphatic filiariasis in Kenya and other sub-Saharan Africa countries demonstrate the capacity of African leadership in NTD control and elimination efforts.